The protective effect of remote ischemic conditioning is lost in patients with hypercholesterolemia - Kövamees, Oskar; Mahdi, Ali; Wodaje, Tigist; Verouhis, Dinos; Brinck, Jonas; Pernow, John (American journal of physiology. Heart and circulatory physiology, 2022)
We investigated the impact of hypercholesterolemia on the protective effect of RIC on ischemia-reperfusion injury in a well-characterized patient population with isolated hypercholesterolemia. The results show that the protective effect of RIC is absent in patients with hypercholesterolemia but is apparent in patients with hypercholesterolemic following treatment with lipid-lowering drugs. The results are of importance for the understanding of how comorbidities affect the therapeutic potential of RIC. Remote ischemic conditioning (RIC), brief repetitive cycles of ischemia and reperfusion in remote tissues, is known to induce robust protection against myocardial ischemia-reperfusion (I/R) injury in preclinical studies. However, translation of the beneficial effects to the clinical setting has been challenging. A possibility is that comorbidities, including hypercholesterolemia, interfere with the protective mechanisms of RIC. The aim of this study was to test if hypercholesterolemia attenuates the efficacy of RIC in patients with hypercholesterolemia. Patients with familial hypercholesterolemia (FH) with high (≥5.5 mmol/L) low-density lipoprotein cholesterol (LDL-C), FH with low (≤2.5 mmol/L) and healthy control subjects ( n = 12 in each group) were included. Flow-mediated vasodilatation (FMD) of the brachial artery was evaluated, before and after a 20-min period of forearm ischemia and 20 min reperfusion (I/R) as a measure of endothelial function. Study subjects were randomized to a RIC protocol consisting of four cycles of 5 min of leg ischemia or sham using a crossover design. Forearm I/R induced significant reduction in FMD in all three groups during the sham procedure. RIC protected from endothelial dysfunction induced by forearm ischemia-reperfusion in healthy controls [FMD baseline 2.8 ± 2.3 vs. FMD after I/R + RIC 4.5 ± 4.0%; means (SD)] and in patients with FH with low LDL-C (4.5 ± 3.5 vs. 4.4 ± 4.2%). By contrast, RIC fails to protect against I/R-induced endothelial dysfunction in patients with FH and high LDL-C (3.9 ± 3.0 vs. 1.1 ± 1.5%; P < 0.01). These findings provide the first evidence in humans that the protective effect of RIC is lost in patients with elevated cholesterol. NEW & NOTEWORTHY We investigated the impact of hypercholesterolemia on the protective effect of RIC on ischemia-reperfusion injury in a well-characterized patient population with isolated hypercholesterolemia. The results show that the protective effect of RIC is absent in patients with hypercholesterolemia but is apparent in patients with hypercholesterolemic following treatment with lipid-lowering drugs. The results are of importance for the understanding of how comorbidities affect the therapeutic potential of RIC.